Discourse Study of the Rejection News of the Implementation Haji Bawakaraeng Ritual on Social Media - Reski Hanisa; Andi Samsu Rijal; Dahniar Dahniar (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
The Bawakaraeng Hajj ritual in South Sulawesi is an important tradition practiced by indigenous communities at the peak of Mount Bawakaraeng. This study explored issues related to the reporting of the Bawakaraeng Hajj ritual on social media. Using critical discourse analysis (CDA) as outlined by Teun A. van Dijk (1993), the research took a qualitative approach based on Digital Ethnography. Between 2022 and 2025, the study identified fourteen data sets from Instagram and Facebook, featuring images, videos, and narratives. The findings revealed two main discourses: one focused on tradition preservation, emphasizing the ritual as a vital part of cultural heritage, and the other addressing religious deviation, viewing the ritual as potentially misaligned with Islamic teachings. The analysis showed that the social media discourse about the Bawakaraeng Hajj reflects the indigenous practices of the region, contributing to its spiritual heritage and local mythology. It highlighted the importance of cultural sustainability and community identity. From a broader perspective, the discourse presented themes related to visual representation and responses to religious concerns. Different narratives emerged from those who accepted and rejected the ritual, providing insights into the community's dynamics. Additionally, the language used in the posts offered a descriptive account of the Haji Bawakaraeng ritual and critiques of opposing views. This study encourages further discussions about how traditional practices can coexist within modern religious contexts.